Edukasi GERD pada siswa SMK Kesehatan Purworejo - Dyah Anggraeni Budhi Pratiwi; Syukriyana Nurul Fadhilah; Dwi Kurniawati Sambodo; Tutik Wahyuningsih (Universitas Mataram, 2026)
Gastroesophageal Reflux Disease (GERD) is a gastrointestinal disorder in which the stomach contents are repeatedly refluxed into the esophagus, causing several symptoms and complications. GERD is a health problem that can reduce the quality of life of patients, so GERD treatment can significantly improve quality of life. Providing education is expected to improve the quality of life of people with GERD. The activity method includes education about GERD with pretest and posttest. This activity was attended by X Pharmacy class totaling 24 students and obtained the results of the average pretest score obtained was 75.4%, while the posttest results obtained an average result of 81.2%. These results show an increase in the understanding and knowledge of students at SMK Kesehatan Purworejo about GERD and its treatment and show the success of this educational activity.